Predicting impacts of future climate change on the distribution of the widespread selaginellas (Selaginella ciliaris and S. plana) in Southeast Asia - AHMAD DWI SETYAWAN; JATNA SUPRIATNA; NISYAWATI NISYAWATI; SUTARNO SUTARNO; ILYAS NURSAMSI (Biodiversitas Journal of Biological Diversity, 2018)
Setyawan AD, Supriatna J, Nisyawati, Sutarno, Sugiyarto, Nursamsi I. 2018. Predicting impacts of future climate change on the distribution of the widespread selaginellas (Selaginella ciliaris and S. plana) in Southeast Asia. Biodiversitas 19: 1960-1977. The current global climate is moving towards dangerous and unprecedented conditions that have been seen as a potentially devastating threat to the environment and all living things.  Selaginella is a fern-allies that needs water as a medium for fertilization, hence its distribution is presumed to be affected by climate change. In Southeast Asia (SEA), there are two widely distributed selaginellas, namely Selaginella ciliaris and S. plana. S. ciliaris is a small herb (up to 4 cm), annual, abundant during the rainy season, and found in the middle-high plains, whereas S. plana is a stout large herb (up to 80 cm), perennial, and mainly found in the lowlands. The purpose of this study was to determine the potential niche distribution of S. ciliaris and S. plana under current climatic conditions, and to predict its future distribution under the impacts of climate change. We used Maxent software along with bioclimatic, edaphic, and UV radiation variables to model the potential niche distribution of those two selaginellas under current and future predictions climate conditions. We generated future predictions under four detailed bioclimatic scenarios (i.e., RCP 2.6, RCP 4.5, RCP 6.0, and RCP 8.5) over three times intervals (2030, 2050, 2080). The results showed that future climatic conditions in the SEA had been predicted to significantly disrupt the distribution of suitable habitat of S. ciliaris and S. plana, and alter their geographic distribution patterns. Although some areas were predicted to become suitable habitat in the early period of future climate change, the overall projections show adverse effects of future climate conditions on the suitable habitat distribution of S. ciliaris and S. plana, as estimated losses of suitable habitat will be higher than the gains.